"Unleaded" Perovskites: Status Quo and Future Prospects of Tin‐Based Perovskite Solar Cells. Issue 47 (1st October 2018) - Ke, Weijun; Stoumpos, Constantinos C.; Kanatzidis, Mercouri G.
Abstract: The tremendous interest focused on organic–inorganic halide perovskites since 2012 derives from their unique optical and electrical properties, which make them excellent photovoltaic materials. Pb‐based halide perovskite solar cells, in particular, currently stand at a record efficiency of ≈23%, fulfilling their potential toward commercialization. However, because of the toxicity concerns of Pb‐based perovskite solar cells, their market prospects are hindered. In principle, Pb can be replaced with other less‐toxic, environmentally benign metals. Sn‐based perovskites are thus the far most promising alternative due to their very similar and perhaps even superior semiconductor characteristics. After years of effort invested in Sn‐based halide perovskites, sufficient breakthroughs have finally been achieved that make them the next runners up to the Pb halide perovskites. To help the reader better understand the nature of Sn‐based halide perovskites, their optical and electrical properties are systematically discussed. Recent progress in Sn‐based perovskite solar cells, focusing mainly on film fabrication methods and different device architectures, and highlighting roadblocks to progress and opportunities for future work are reviewed. Finally, a brief overview of mixed Sn/Pb‐based systems with their anomalous yet beneficial optical trends are discussed. The current challenges and a future outlook for Sn‐based perovskites are discussed. Abstract : Low‐toxicity tin‐based perovskites have excellent optical and electrical properties, and are a good alternative for lead‐based perovskites. However, the performance and stability of tin‐based perovskites are not comparable. The properties of tin‐based perovskite films and the performance of tin‐based perovskite solar cells are reviewed. The current challenges and a future outlook for Sn‐based perovskites are discussed.